Relevansi Kriteria Penilaian Desa/Kelurahan Sadar Hukum Terhadap Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Ahmad Fauzi, Dwi Wahyu; Wahyuni, Sri (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2022)
This research examines the criteria for Law-Aware Villages/Kelurahan Sadar Hukum which are implemented based on Circular Letter of the Head of the National Law Development Agency (BPHN) Number PHN-05.HN.04.04 of 2017 concerning Changes in Criteria for Assessment of Law-Aware Villages/Kelurahan Sadar Hukum. The embryo of legal awareness comes from the community and the closest point to the community are those in villages and sub-districts. Law Conscious Villages are a manifestation of legal development directed towards a national legal system based on Pancasila and the 1945 Constitution of the Republic of Indonesia, in accordance with the ideals and objectives of the enactment of Law Number 17 of 2007 concerning the National Long-Term Development Plan 2005-2025, which is explained in the appendix at the point of realizing a democratic Indonesia based on law. Law-Aware Villages are a facilitation of the implementation of the constitutional mandate of Article 1 paragraph (3) and Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The criteria for Law Aware Villages based on the Circular Letter of the Head of the National Law Development Agency (BPHN) Number PHN-05.HN.04.04/2017 consists of the dimensions of access to legal information, legal implementation, access to justice, access to democracy and regulation. This program aims to build a culture of legal awareness in the community. The implementation of the Legal Aware Village/Kelurahan is expected to provide a realization in the national legal system in accordance with Pancasila and the 1945 Constitution of the Republic of Indonesia.